The urban matrix and artificial light restricts the nightly ranging behaviour of Gould's long‐eared bat (Nyctophilus gouldi). (29th April 2013) - Threlfall, C. G.; Law, B.; Banks, P. B.
Abstract Cities are heterogeneous landscapes, with remnant vegetation interspersed amongst areas designed for human use. Native wildlife remaining in urban areas are only likely to thrive and persist if they incorporate human altered areas into what they perceive as habitat. Many sensitive species may be lost if they are restricted to remnant vegetation, and cannot use the urban matrix. In this study, we quantify spatial aspects of the ranging behaviour of Gould's long‐eared bat (Nyctophilus gouldi) using radio‐telemetry and acoustic surveys to determine use of the suburban–bushland interface. This species represents a group prone to extinction due to biological attributes that adapt it to flight within cluttered vegetation, making it more specialized. We radio‐tracked 19 individuals in Cumberland State Forest (CSF), a 40‐ha remnant located in north‐west Sydney, New South Wales, Australia. The nightly range (95% Kernel Density Estimator) was small and localized, and was no greater than 80 ha, where individuals moved on average less than 300 m from roosts each night. All individual N. gouldi tracked used bushland in an almost obligate manner, where up to 100% of used habitat was within local bushland, with little to no use of areas classified as 'urban' (residential, commercial and educational land uses). Small open spaces exposed to artificial lighting within the main ranging area of CSF had significantly lower activity (bat passes) of Nyctophilus spp. and significantly higher activity of other species more tolerant of urbanization (P < 0.05). Our results demonstrate that artificial lighting can 'spill‐over' into bushland and alter the use of preferred habitat. We conclude that large patches (>40 ha) of protected remnant vegetation must be managed to reduce further degradation, and smaller isolated patches could be restored to provide habitat, particularly in narrow bushland corridors, to assist these species to tolerate urban areas.